2018
DOI: 10.5539/jel.v7n4p262
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Views about the Teacher Training Program for Gifted Education

Abstract: Gifted children are a special group within the scope of the special education so it is needed to be used by a number of special techniques and teaching methods. However, most teachers do not receive any training about gifted students. This situation-teachers lack of necessary education-can cause gifted students to underachieve or quit the school. The number and variety of professional tranings on gifted students is rather limited. In the study, a teacher training program which aimed to provide teachers experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 13 publications
(13 reference statements)
1
9
0
4
Order By: Relevance
“…The trainers, the school counselors, and trainees expressed that the duration of the training program was too short for beginner in-service teachers to acquire enough knowledge on the education of the gifted students. Similar research results are found in the research of Sayı (2018) where participated teachers stated that was needed to have more time to carry out such training. The training hours were very few to cover-up the curriculum standards, for the personalized teaching in cases that was needed, and for practice on the training of gifted students, which required specific authorization by the Ministry of Education.…”
Section: Recommendationssupporting
confidence: 84%
See 1 more Smart Citation
“…The trainers, the school counselors, and trainees expressed that the duration of the training program was too short for beginner in-service teachers to acquire enough knowledge on the education of the gifted students. Similar research results are found in the research of Sayı (2018) where participated teachers stated that was needed to have more time to carry out such training. The training hours were very few to cover-up the curriculum standards, for the personalized teaching in cases that was needed, and for practice on the training of gifted students, which required specific authorization by the Ministry of Education.…”
Section: Recommendationssupporting
confidence: 84%
“…Results of various studies have shown that training future teachers for the education of gifted and talented students has increased their understanding of the sense of giftedness, and has helped them evaluate their personal interests and abilities that would lead them to self-reflective awareness (Kabadayi, 2016) but research on or evaluation of the effects of these training models is meager (Choe, 2011(Choe, , 2016Sayı, 2018;Tortop, 2014). Studies (Hansen & Feldhusen, 1994;Mönks & Pfluger, 2005) indicated that teachers that were trained in gifted education were more competent and created a friendly classroom environment in comparison with the ones that didn"t have any training in this field.…”
Section: Training As a Model Of Professional Developmentmentioning
confidence: 99%
“…An online training program given by Leana-Tascilar et al (2016) to parents of gifted children showed a significant increase in their level of awareness. Sayi (2018) who conducted a training program for teachers with gifted students also found that these teachers feel that they lack of informarion about giftedness. The training program received positive opinions from teachers and they wished that it could be conducted longer.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to BILSEM (Bilim ve Sanat Merkezi-Science and Art Centers), there exist resource rooms [MoNE (Milli Eğitim Bakanlığı), 2015] catering to the needs of primary and secondary level gifted students. Those gifted students whose special situations have not been diagnosed or whose cognitive development has not been supported despite being diagnosed are prone to suffer from both cognitive and emotional problems including anxiety disorders, eating disorders, loneliness, isolation, low self-esteem related to being different, dissatisfaction, perfectionism, hyperactivity, inclination to commit a crime, communicative disorders and asociality (Sayı, 2018). Therefore, it is essential that gifted individuals' interests, characteristic traits and problem areas must be identified; and precautions and support be provided accordingly (Akpolat, Demirok and Seven, 2017).…”
Section: Purpose and Significancementioning
confidence: 99%
“…Bu sınırlılık, özel yetenekli öğrencilerin kendilerini gerçekleştirme gereksinimlerini engellediği gibi, aynı zamanda gelişimlerini geriletebilme riski yaratmakta ve onların sosyal-duygusal gelişim sorunları yaşamalarına neden olabilmektedir. Bilişsel ve duyuşsal gelişimleri desteklenmeyen özel yetenekli öğrencilerin bir bölümünde kaygı sorunları, yeme bozuklukları, zorbalık, yalnızlık, soyutlanma ve farklı olmaya ilişkin düşük benlik saygısı, tatminsizlik, olumsuz mükemmeliyetçilik, aşırı hareketlilik, suça yönelme, iletişim bozukluğu ve asosyalleşme gibi hem bilişsel hem de duyuşsal sorunlar ortaya çıkabilmektedir (Sayı, 2018). Nitekim özel yetenekli bireylerin ilgi alanları, belirgin özellikleri ve sorunları belirlenerek bu özelliklere uygun önlemlerin alınması ve desteklerin sağlanması gerekir (Akpolat, Demirok ve Seven, 2017).…”
unclassified